Co-transfer of tumor-specific effector and memory CD8+ T cells enhances the efficacy of adoptive melanoma immunotherapy in a mouse model. Issue 1 (29th May 2018) - Contreras, Amanda; Beems, Megan V.; Tatar, Andrew J.; Sen, Siddhartha; Srinand, Prakrithi; Suresh, M.; Luther, Tahra K.; Cho, Clifford S.
Abstract : Background: Adoptive cell transfer (ACT) is a promising cancer immunotherapeutic strategy that remains ineffective for a large subset of patients. ACT with memory CD8+ T cells (Tmem ) has been shown to have superior efficacy compared to traditional ACT with effector CD8+ T cells (Teff ). Teff and Tmem have complementary physiological advantages for immunotherapy, but previous publications have not examined ACT using a combination of Teff and Tmem . Methods: Splenocytes harvested from Ly5.1+/C57BL/6 mice during and after infection with lymphocytic choriomeningitis virus (LCMV) were used to generate bona fide effector and memory CD8+ T cells specific for the LCMV epitope peptide GP33. Congenic Ly5.2+/C57BL/6 mice were inoculated with B16F10 melanoma cells transfected to express very low levels of GP33, then treated with ACT 7 days later with GP33-specific Teff, Tmem, or a combination of Teff  + Tmem . Results: Inhibition of melanoma growth was strongest in mice receiving combinatorial ACT. Although combinatorial ACT and memory ACT resulted in maximal intratumoral infiltration of CD8+ T cells, combinatorial ACT induced stronger infiltration of endogenous CD8+ T cells than Tmem ACT and a stronger systemic T cell responsiveness to tumor antigen. In vitro assays revealed rapid but transient melanoma inhibition with Teff and gradual but prolonged melanoma inhibition with Tmem ; the addition of Tmem enhanced the ability of Teff to inhibit melanoma in a manner that could be reproduced using conditioned media from activated Tmem and blocked by the addition of anti-IL-2 blocking antibody. Conclusions: These findings suggest that a novel combinatorial approach that takes advantage of the unique and complementary strengths of tumor-specific Teff and Tmem may be a way to optimize the efficacy of adoptive immunotherapy.